2010
DOI: 10.1002/jcb.22510
|View full text |Cite
|
Sign up to set email alerts
|

Vasostatin 1 activates eNOS in endothelial cells through a proteoglycan‐dependent mechanism

Abstract: Accumulating evidences point to a significant role for the chromogranin A (CgA)-derived peptide vasostatin 1 (VS-1) in the protective modulation of the cardiovascular activity, because of its ability to counteract the adrenergic signal. We have recently shown that VS-1 induces a PI3K-dependent-nitric oxide (NO) release by endothelial cells, contributing to explain the mechanism of its cardio-suppressive and vasodilator properties. However, the cellular processes upstream the eNOS activation exerted by this pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…9 Experimental evidence suggests that CgA1-78 can interact with heparan sulfate proteoglycans on endothelial cells and increase caveolae-dependent endocytosis. 36 CgA1-78 can also interact with membrane phospholipids, particularly with phosphatidylserine, an anionic phospholipid exposed on the surface of tumor endothelial cells, 10,[37][38][39] and inhibit VEGF-induced phosphorylation of ERK, an enzyme crucial for the induction of a cascade of events leading to increased cell proliferation and migration in angiogenesis. 40,41 In addition, CgA1-78 can inhibit TNF-induced phosphorylation of p38-MAPK by a pertussis toxin sensitive mechanism, a pathway important for the disassembly of adherence junctions in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…9 Experimental evidence suggests that CgA1-78 can interact with heparan sulfate proteoglycans on endothelial cells and increase caveolae-dependent endocytosis. 36 CgA1-78 can also interact with membrane phospholipids, particularly with phosphatidylserine, an anionic phospholipid exposed on the surface of tumor endothelial cells, 10,[37][38][39] and inhibit VEGF-induced phosphorylation of ERK, an enzyme crucial for the induction of a cascade of events leading to increased cell proliferation and migration in angiogenesis. 40,41 In addition, CgA1-78 can inhibit TNF-induced phosphorylation of p38-MAPK by a pertussis toxin sensitive mechanism, a pathway important for the disassembly of adherence junctions in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that wortmannin blockade of the PI3K pathway abolished the CST-induced effects on inotropism and lusitropism. This suggests that, at least in part, the CST cardiotropism is achieved through this novel signaling pathway expected for receptor-orphan peptides with membrane-interacting properties, like CST (61).…”
Section: ␤-Adrenergic and Et-1 Involvementmentioning
confidence: 96%
“…Concentrations of vasostatin-1 and -2 in these experiments were chosen according to the previous literature. 30,31 Although higher than concentrations measured in vivo, the biological significance of such concentrations is in the possibility that tissue concentrations of these peptides are higher than plasma concentrations, and in the possibly lower biological activity of prokaryotic recombinant proteins here used (in this case from E. coli BL21) compared with eukaryotic proteins. In control cells, these proinflammatory factors induced a significant increase in VCAM-1, ICAM-1, and E-selectin expression ( Figure 5 and Supplementary material online, Figures S2 and S3).…”
Section: Effects Of Vasostatin-1 and Vasostatin-2 In Vitro In Cell Exmentioning
confidence: 97%